1999
DOI: 10.1080/14622299050011441
|View full text |Cite
|
Sign up to set email alerts
|

Smokers' sex and the effects of tobacco cigarettes: Subject-rated and physiological measures

Abstract: Smoking tobacco cigarettes results in characteristic subject-rated and physiological effects in regular tobacco smokers. Few reports have investigated potential sex differences in the physiological and subjective effects produced by tobacco smoking, though previous reports indicate that men and women differ in their tobacco smoking behavior. Sex differences in the subjective and/or physiological effects of smoking may help determine why women find quitting smoking more difficult than men and may help guide gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
79
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 33 publications
7
79
0
1
Order By: Relevance
“…The TCQ data showed the same pattern; only women reported significantly less tobacco craving following nicotine administration across Nicotine effects on mood and cognition CS Myers et al sessions. Similarly, Eissenberg et al (1999) found that, after smoking two cigarettes, women reported significantly less desire to smoke than men. Others also have noted sex differences in subjective response to nicotine.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The TCQ data showed the same pattern; only women reported significantly less tobacco craving following nicotine administration across Nicotine effects on mood and cognition CS Myers et al sessions. Similarly, Eissenberg et al (1999) found that, after smoking two cigarettes, women reported significantly less desire to smoke than men. Others also have noted sex differences in subjective response to nicotine.…”
Section: Discussionmentioning
confidence: 88%
“…For example, File et al (2001) reported that women nonsmokers reported feeling less physically tired and men more tired after receiving 2 mg intranasal nicotine. Eissenberg et al (1999) found that, after smoking, women reported significantly less restlessness, sedation, and difficulty concentrating than men. Women have reported more positive subjective responses to nicotine when it was administered by smoking compared with nasal spray (Perkins et al, 1994).…”
Section: Discussionmentioning
confidence: 94%
“…Although findings for Factor 2 of the QSU-Brief were not significant, there is growing evidence that assessing multiple aspects of urges allows for a more thorough measurement of this construct. Indeed, there are numerous studies that have revealed differential outcomes across both factors of the QSU (Burton and Tiffany, 1997;Corrigall et al, 2001;Eissenberg et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together with duration, puff velocity determines puff volume that predicts nicotine delivery in cigarette smokers. 24 The average puff velocity of tobacco cigarette smokers is generally 29-38 ml/s 18,28,29 though experienced ECIG users may draw lower puff velocities. 30 To date, no study has examined the combined influence of puff duration and velocity on nicotine yield in ECIG aerosol.…”
Section: Introductionmentioning
confidence: 99%